Frequent Limits and Advantages of Conditions for Geology Education: Example of Czech and Slovak State Curricula - Tereza Jedličková; Andrea Svobodová; Václav Kachlík (Center for Educational Policy Studies Journal)
Geology is a subject of low interest for many pupils and teachers. The present study aims at examining the organizational conditions for geology education using the model of the Czech Republic and Slovakia, drawing from the national curricula. The study discusses the possible reasons for the unpopularity of the field worldwide and proposes general recommendations that would contribute to increasing interest in geoscience. The main drawbacks of geology education seem to be the large volume of required knowledge, its thematic structure, and a lack of links to real life. The Czech curriculum is vaguely and theoretically defined, placing demand on pupils, especially in the area of memorizing given information and practically pays no attention to recommended teaching methods. In contrast, the Slovak curriculum better reflects current trends. In general, it is necessary to implement continuous educational support for geology teachers and restructure the geology syllabus so that individual sub-fields are interlinked. Moreover, the learning outcome definition should include action-based education, fieldwork, experimenting, and similar elements.